2017
DOI: 10.1089/apc.2016.0265
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Violence Victimization on Sexual Health Behaviors and Outcomes

Abstract: This study examines the implications of a history of personal violence on health and health behaviors. A secondary analysis of cross-sectional data involving adults (n = 214) from a semirural area in southern Louisiana between October 2008 and December 2010 was conducted to ascertain the association between a personal history of violence victimization and indicators of sexual health behaviors and outcomes: communication with sexual partners about HIV status, consistent condom use, and sexually transmitted infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The level of emotional and physical violence or intimidation suffered during the SV episode, the sometimes recurrent nature of exposure, the role of multiple and/or known perpetrators, the early age of the victim, and finally the lack of emotional support provided after the episode, all have an important impact on the short and long-term outcomes of SV 1 . In this context, lifetime risk of STIs was shown higher after a SV episode [7][8][9][10][11][12] . Several intertwining factors could mediate risky sexual behavior among SV victims: multiple sexual partners, inconsistent condom use, lack of access to STIs treatment, mental disorders (depression and anxiety), severity of alcohol and illicit drug abuse [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of emotional and physical violence or intimidation suffered during the SV episode, the sometimes recurrent nature of exposure, the role of multiple and/or known perpetrators, the early age of the victim, and finally the lack of emotional support provided after the episode, all have an important impact on the short and long-term outcomes of SV 1 . In this context, lifetime risk of STIs was shown higher after a SV episode [7][8][9][10][11][12] . Several intertwining factors could mediate risky sexual behavior among SV victims: multiple sexual partners, inconsistent condom use, lack of access to STIs treatment, mental disorders (depression and anxiety), severity of alcohol and illicit drug abuse [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, lifetime risk of STIs was shown higher after a SV episode [7][8][9][10][11][12] . Several intertwining factors could mediate risky sexual behavior among SV victims: multiple sexual partners, inconsistent condom use, lack of access to STIs treatment, mental disorders (depression and anxiety), severity of alcohol and illicit drug abuse [9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the sex without coercion was associated with a more frequent condom use [20]. The correlation between victimization and sexual risk-related behaviors is well established, the supposed mechanism being weakened assertiveness [21].…”
Section: Casementioning
confidence: 99%
“…Previous studies have concluded that generally CSA survivors engage in risker sexual behaviors (Abajobir et al, 2017) and experience further episodes of sexual victimization (Krahé & Berger, 2017;Ports et al, 2016)another risk factor for HIV and STIs (Latimer et al, 2017). Research on female CSA survivors has reported that the experience of being abused can lead to long patterns of oversexualization and undersexualization (Slavin et al, 2020), information which is limited among men, MSM, and YMSM.…”
mentioning
confidence: 99%